Opt in versus opt out: a free-entry analysis of privacy policies - Jan Bouckaert; Hans Degryse (Center for Economic Studies and ifo Institute (CESifo), 2006)
There is much debate on how the flow of information between firms should be organized, and whether existing privacy laws should be amended. We offer a welfare comparison of the three main current policies towards consumer privacy anonymity, opt in, and opt out within a two-period model of localized competition. We show that when consumers find it too costly to opt in or opt out, privacy policies shape firms' ability to collect and use customer information, and affect their pricing strategy and entry decision differently. The free-entry analysis reveals that social welfare is non-monotonic in the degree of privacy protection. Opt out is the socially preferred privacy policy while opt in socially underperforms anonymity. Consumers never opt out and choose to opt in only when its cost is sufficiently low. Only when opting in is cost-free do the opt-in and opt-out privacy policies coincide.
Keywords: D11; 330; Datenschutz; Betriebliches Informationssystem; Customer Relationship Management; Theorie